Outcomes of Laser Photocoagulation for Goldberg Stage 3 Proliferative Sickle Cell Retinopathy (PSR) in an Eye Foundation Hospital: A Review - Oderinlo Olufemi; Bulus Stanley Sano; Umeh Victor; Lateefat Oshunkoya; Adekunle Hassan (Medical Science: Trends and Innovations Vol. 4, 2025)
Background: Sickle cell disease consists of a group of inherited hemoglobinopathies affecting multiple organs including the eyes. Ischemia can result from occlusion of vessels by rigid red blood cells with a sickle-shaped appearance. Aims and objectives: The aim of the study is to report regression of retina neovascularization and visual outcomes after prophylactic scatter retina laser photocoagulation for Goldberg stage 3 PSR in a tertiary private hospital in sub-Saharan Africa. Methods: A retrospective review of case files of patients who were treated with prophylactic scatter retina laser photocoagulation between January 2017 and June 2022 following a diagnosis of PSR in a Eye Foundation Hospital, Ikeja, Lagos, Nigeria, was done. Results: A total of 124 eyes of 62 patients with PSR were seen within the period under consideration. A majority of patients (49 (79.0%)) had hemoglobin (Hb) genotype SC, while 13 patients (21%) were Hb genotype SS. At presentation, 29 eyes (23.3%) had Goldberg stage 2 PSR, 55 eyes (44.4%) had Goldberg stage 3 PSR, 27 eyes (21.8%) had stage 4 PSR, and 13 eyes (10.5%) had stage 5 PSR. All 55 eyes (49.2%) with stage 3 PSR were treated with prophylactic retina laser photocoagulation. At the patients’ last clinic visit, 34 eyes (61.8%) had the same visual acuity (VA) as at presentation, 11 eyes (20%) had improvements in VA, while 10 eyes (18.2%) had worse VA. Laser treatment success (regression of seafan neovascularization) was seen in 50 eyes (90.9%), while five eyes (8.1%) had unsuccessful laser treatment. Conclusion: A high percentage (90.9%) of resolution of retina neovascularization secondary to PSR at stage 3 of Goldberg’s classification was seen after prophylactic scatter retina laser photocoagulation in our group of evaluated patients. Most patients (81.8%) maintained or had improvements in their visual acuities over the period of follow-up. More clinical research is required to further evaluate outcomes of laser photocoagulation for PSR. In conclusion, a high percentage (90.9%) of resolution of retina neovascularization secondary to PSR at stage 3 of Goldberg’s classification was seen after prophylactic scatter retina laser photocoagulation in our group of evaluated patients.